ANALISIS HUBUNGAN IPM, KAPASITAS FISKAL, DAN KORUPSI TERHADAP KEMISKINAN DI INDONESIA (STUDI KASUS 38 KABUPATEN/KOTA DI INDONESIA TAHUN 2008 DAN 2010) - Septina Franciari, Purwiyanti; Sugiyanto, FX. (Diponegoro Journal of Economics, 2013)
ABSTRACTPoverty remains the biggest problem for Indonesia. Therefore, it is necessary to find solutions to overcome, or at least to reduce the level of poverty in Indonesia. This study aimed to analyze the effect of HDI, economic capacity, and corruption on poverty in Indonesia.The method used in this study are OLS (Ordinary Least Square) and granger causality test using secondary data types. Research samples are 38 regencies/cities in Indonesia in 2008 and 2010.The results of this study show that in 2008 HDI, fiscal capacity, and corruption have negative effect that not significant at Î± = 5 percent and Î± = 10 percent against poverty. In 2010, the fiscal capacity has negative effect that significant at Î± = 10 persent against poverty, while HDI and corruption have negative effect that not significant. Based on the results of granger causality, there are diferences in behavior patterns between 2008 and 2010.